New method to estimate the cycling frontal area - Debraux, P.; Bertucci, W.; Manolova, A. V.; Rogier, S.; Lodini, A. (International Journal of Sports Medicine, 2009)
The purpose of this study was to test the validity and reliability of a new method to estimate the projected frontal area of the body during cycling. To illustrate the use of this method in another cycling speciality (i.e. mountain bike), the NM data were coupled with a powermeter measurement to determine the projected frontal area and the coefficient of drag in actual conditions. Nine male cyclists had their frontal area determined from digital photographic images in a laboratory while seated on their bicycles in two positions:Upright Position (UP) and Traditional Aerodynamic Position (TAP). For each position, the projected frontal area for the body of the cyclist as well as the cyclist and his bicycle were measured using a new method with computer aided-design software, the method of weighing photographs and the digitizing method. The results showed that no significant difference existed between the new method and the method of weighing photographs in the measurement of the frontal area of the body of cyclists in UP (p=0.43) and TAP (p=0.14), or between the new method and the digitizing method in measurement of the frontal area for the cyclist and his bicycle in UP (p=0.12) and TAP (p=0.31). The coefficients of variation of the new method and the method of weighing photographs were 0.1% and 1.26%, respectively. In conclusion, the new method was valid and reliable in estimating the frontal area compared with the method of weighing photographs and the digitizing method.